Depression and anxiety in asthma patients attending a tertiary care centre in north Kerala: a cross-sectional study - Nair, Swetha C.; Kottarathil, Manoj Dehandath; K., Muhammad Shafeek; Mavila, Rajani; Veetil, Padmanbhan Kadammar (International Journal of Research in Medical Sciences, 2022)
Background: Asthma is a common chronic non-communicable disease that causes substantial burden to people, often causing a reduced quality of life, not only due to its physical effects, but also its psychological and social effects. Objectives were to assess the prevalence of depression and anxiety in patients with stable asthma in a tertiary care centre. to assess the relationship between bronchial asthma symptom control and degree of depression and anxiety. To assess the quality of life in asthma patients. Methods: It was a cross-sectional study conducted in govt. medical college, Kannur for 1 year duration. The 150 patients with stable asthma, attending the outpatient clinic of department of chest diseases, satisfying inclusion criteria were included in the study. The socio demographic details and the relevant clinical details were collected using the socio demographic proforma. Spirometry was done for all patients. Quality of life of these patients was assessed with standardized asthma quality of life questionnaire-Malayalam version. For psychological status, (HADS) 23 scale was used. Results: We found 33 patients (22%) to have depression and 33 (22%) patients to have anxiety among stable asthma patients. AQLQ scores were assessed and obtained a median of 4.92, interquartile range of 5.0. The median AQLQ scores among patients with no anxiety and depression was 5.56. The median AQLQ score among patients with depression and anxiety was 3.400. There was significant correlation between the control of asthma with AQLQ score. Conclusions: Depression and anxiety is substantially related to quality of life, and hospitalization in asthma patients.